Taxpayer Compliance and Fiscal Depreciation Treatment of Assets in Achieving Legal Certainty of Corporate Income Tax - Ali Maskan; Marno Nugroho; Ari Pranaditya (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
Purpose – This research aims to analyze how taxpayer behavioral factors (Compliance) and technical taxation factors (Treatment of Fiscal Asset Depreciation) simultaneously influence Legal Certainty in determining Corporate Income Tax (CIT) in Indonesia. Methodology – This study employs a normative legal research method with a statutory approach through the analysis of the Law on General Provisions and Tax Procedures (UU KUP), the Income Tax Law (UU PPh), and the Tax Harmonization Law (UU HPP) as primary legal foundations. Findings – The results indicate that Legal Certainty in Corporate Income Tax is achieved through the synergy of Taxpayer Compliance levels, which minimize dispute risks (Dewi et al., 2025), and the precision of Fiscal Asset Depreciation treatment through accurate fiscal reconciliation in accordance with Minister of Finance Regulation (PMK) No. 72 of 2023 (Aryani & Romanda, 2023). Implications – This research emphasizes the significance of harmonization between taxpayer awareness education and the clarity of technical regulations concerning asset depreciation. Originality – This paper integrates behavioral aspects and technical tax accounting into a single conceptual framework for tax legal certainty.